Pre-clinical evaluation of effectiveness of infusion solutions with different osmolarity during acute blood loss in experiments on rats - I. А. Shperling; А. V. Krupin; N. K. Arokina; О. А. Rogov (Сибирский научный медицинский журнал, 2024)
The aim of the research was to experimentally evaluate the effectiveness of infusion solutions with different osmolarity during acute blood loss in experiments on rats. Material and methods. Experiments approved by the local Ethics Committee, have been done on 30 male rats line Vistar (320 ± 35 g). Design of the research included anesthesia, simulation of acute blood loss to 50 % of circulating blood volume, its replenishment with experimental infusion solutions based on polyglycan derivatives (estimated osmolarity 1026.6, 1784.2, 2566.6 mOsm/l), research of survivability, functional state of cardiovascular and respiratory systems, blood acid-base status and gas partial pressure 5, 30, 60, 120, 180 min after the beginning of replenishment of circulating blood volume. The infusion solution Hemostabil was used as a comparison product. Results. The highest survival rate, restoration of hemodynamics and acid-base state and blood acid-base status and gas partial pressure were obtained as a result of infusion of solution with osmolarity 1026.6 mOsm/l. In this group of animals survivability accounted for 100 %, arterial pressure restored in 5 minutes after the start of infusion, indicators of blood acid-base status and gas partial pressure normalized in 120 min of experiment. All of the results had statistically significant differences (p < 0.05) relative to values in other experimental groups. Conclusions. Sample of solution with osmolarity 1026.6 mOsm/l is the most effective in restoration of hemodynamics of rats with the blood loss up to 50 % of circulating blood volume. The expediency of the researches of safety of this infusion solution based on polyglucan derivatives in the capacity of medication for replenishment acute blood loss is substantiated.